The Development Technological Pedagogical and Content Knowledge Substitution, Augmentation, Modification, Redefinition Textbooks to Improve Digital Skills - Maisarah Maisarah; Cut Kumala Sari; Mahlianurrahman Mahlianurrahman; Cyndi Prasetya; Febrina Putri; Intan Nazira Br Sembiring; Nova Yurika (JIPI (Jurnal IPA & Pembelajaran IPA), 2026)
This research is motivated by the need for textbooks. Basic concepts of biology sciencewhich is able to integrate the TPACK approach and the SAMR framework to support 21st-century learning. Problems in the field indicate low digital skills and the teaching materials used do not fully utilize technology optimally. This study aims to develop a textbook, testing its validity, practicality, and effectiveness in improving the digital skills of prospective elementary school teachers. The study uses a development approach with the addie model (analysis, design, development, implementation, evaluation). The research subjects involved 150 PGSD students from the class of 2024. The research instruments were expert validation questionnaires, practicality questionnaires, and digital skill tests. The results of the study showed that the TPACK SAMR-based textbook proved to be very valid and very practical for use for basic concepts of biology in elementary school, even the use of textbooks was very effective in improving the digital skills of prospective elementary school teachers. The novelty of the research lies in the integration of the TPACK approach and the SAMR framework in one applicable textbook for the basic concepts of biology in elementary school. The implications of the research confirm that TPACK-SAMR textbooks can be a model for developing innovative learning media, relevant to the demands of 21st-century education, and contributing to improving the competence of prospective elementary school teachers